Sagittal cranial projections dataset extracted from CBCT volumes corrected to natural head position in a mixed ethnicity population - Carlos Andrés Ferro Sánchez; Cristian Orlando Diaz Laverde; Sandra Esperanza Nope Rodríguez; Juan Fernando Aristizábal; Oscar Iván Campo Salazar (Data in Brief, 2024)
This dataset features 200 sagittal projection images derived from Cone Beam Computed Tomography (CBCT) scans, corrected according to the Natural Head Position (NHP) guidelines proposed by Fredrik Lundström and Anders Lundström. The images originate from orthodontic patients in Cali, Valle del Cauca, Colombia, encompassing both initial phases and ongoing treatments. The dataset is divided into two groups: 100 images from female subjects (CoF) and 100 from male subjects (CoM), facilitating gender-specific studies.The dataset is accompanied by an Excel file ``Data info.xlsx'' that details the rotation angles in the axial (Yaw), coronal (Roll), and sagittal (Pitch) planes, along with the pixel size and image dimensions. This detailed documentation supports the replication of studies and aids in the interpretation of cephalometric analyses.Corrections made to align the images with NHP standards involve adjustments in the three main anatomical planes using points from the frontozygomatic suture (Fz) in the axial and coronal planes, and sella (S) and nasion (N) for the sagittal plane.